KUALITAS PAPAN KOMPOSIT LIMBAH KULIT BATANG SAGU (Metroxylon sp) DAN PLASTIK POLIPROPILENA BERDASARKAN JUMLAH LAPISAN PENYUSUN - Mayang Archila; Farah Diba; Dina Setyawati; . Nurhaida (Universitas Tanjungpura, 2017)
The objective of this research is to evaluate the effect of the number of composite layers on the quality of the composite board from sago bark waste and plastic waste, and the number of composite layers that produce the best quality on composite board. The composite board is made with size 30 cm x 30 cm x 1 cm. The composition and division of the material was carried out manually with the polypropylene distribution divided into three parts: the front and rear respectively of 15%, and the center 70% of the plastic weight. Target density of composite boards was 0.7 g / cm3. The treatment used is based on the number of layers composing, which is 5 layers, 7 layers, 9 layers, 11 layers and 13 layers. After mixed the sago bark particle and waste of polypropylene, the materials then compressed with hot press at 180oC with pressure about ± 25 kg / cm2 for 10 minutes. The composite boards then tested the quality included physical and mechanical properties. Testing of physical and mechanical properties refers to JIS A 5908-2003 standard. Physical properties consist of density, moisture content, thickness swelling, and water absorption. Mechanical properties consist of modulus of rupture, modulus of elasticity, internal bonding, and modulus of screw holding strength. The study used a completely randomized design experiment consisting of 5 treatments and 3 replications. The results showed the average value of composite density was range between 0.6962 – 0.7896 g/cm3, the moisture content was range between 4.3388 % - 6.8066%, the thickness swelling was range between 8.2605% - 11.9615%, and water absorption was range between 17.2380% - 22.3867%. The average value of modulus of rupture was range between 60,0632 kg/cm2 – 64,4068 kg/cm2, the modulus of elasticity was range between 17935,1813g/cm2 – 32841,8278 kg/cm2, the internal bonding was range between 1,9268 kg/cm2 - 5,4119 kg/cm2, and the modulus of screw holding strength was range between 78,2530 kg/cm2 – 92,9677 kg/cm2. The composite board made from sago stem bark waste and polypropylene waste plastic with 13 layers treatment is the best composite board and fulfilled the JIS A 5908-2003 standard. Keywords: bark of sago, composite boards, layer of composite, polypropylenes plastic, waste